Marker assisted rice breeding for resistance to biotic and abiotic stressors - Dubina Elena; Kostylev Pavel; Garkusha Sergey; Ruban Margarita; Pischenko Dmitry (BIO Web of Conferences, 2020)
Due to the fact that blast (causative agent – Pyricularia oryzae Cav.) is considered to be one of the harmful diseases of rice around the world, weeds compete with the crop for light, mineral nutrition and space, the accelerated development of resistant genotypes for these stressors is very relevant. The use of modern biotechnological approaches (molecular marking) is promising and especially in demand in breeding rice varieties of a new generation. This article presents the results on the introduction and pyramiding in the same genotype blast resistance genes Pi-1, Pi-2, Pi-33, Pi-ta, Pi-b, Pi-40 and the gene for tolerance to prolonged flooding Sub 1A, as a weed control factor, based on domestic rice varieties Flagman, Snezhinka, Novator, Boyarin, as well as large-grain lines, with a short growing season VNIIR5242, KP-25-14, KP-163 and VNIIR9678. As a result of the volumetric work using marker control of target genes in the genotypes of hybrid plants, 4 modern varietal samples and more than 400 backcross self-pollinated rice lines with introduced and pyramided blast resistance genes, as well as backcross self-pollinated lines with Pi and Sub1A genes, were obtained. These plants are adapted for cultivation in the south of Russia, have a duration of 115-117 days, a height of 87-100 cm, a mass of 1000 grains – 30 or more grams, a yield of 8.5 – 11 t/ha, which is significantly higher than that of the standard variety Flagman.